Adsorpsi Zat Warna Direct Black 38 Menggunakan Kitosan Hidrogel - Zainal Arifin; Muh. Kasim; Yoga Irawan (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
The dye widely used in sarung samarinda textile dyeing is direct black 38 (DB 38). A batch system applied tostudy the adsorption of DB 38 from aqueous solutions by chitosan hydrogel beads as adsorbent. The ioniccross-linking reagent sodium tripolyphosphate (STTP) used to obtain more rigid chitosan beads. The effectsof contact time and adsorbent dose were evaluated. DB 38 and adsorbent inserted into flasks and wereshaked at 150 rpm using an electric shaker at room temperature. Samples were filtered and analyzed using aUV-Vis at a wavelength of 505.7 nm to determine the concentration of DB 38. The results showed thatchitosan produced in a spherical shape and diameter of 3 mm. The beads observed solid, rigid, white milk,not sticky and has water content of 96%. The use of chitosan hydrogel dose of 0,34 g (dry based) and contacttime of 360 minutes can removal of DB 38 up to 92,42%. The maximum adsorption capacity is 4,93 mg/g,which followed Freundlich model.